The Representation Of Arabian Identity Through Cultural Terms In Arabic Proverbs - Baking, Aad Nur Sayyidus Syuhuur (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
One form of language that contains cultural elements is proverbs which in Arabic are called amtsal. This study aims to discover the identity of the Arabians which is represented in cultural terms in the amtsal. The research method used is descriptive qualitative, while data collection is done by reading and writing. The results show two things; the first, Arabic proverbs contain a number of cultural terms, which consist of three types, namely ecology, socio-culture, and artifacts. The second result shows the Arabic identity as seen from the amtsal, with a total of seven identities, namely the custom of war, fondness of traveling, low rainfall, palm trees and the fruit, gold, value time, and honoring science.